The impact of university entities on students’ loyalty: the mediating role of student satisfaction - Ahmad, Aznita; Mahayuddin, Nafiza; Wan Muhammad Nawi, Wan Nurul Fatimah; Saad, Mazni; Ong, Mohd Hanafi Azman (IIUM Press, 2021)
Student loyalty in the higher education sector helps university administrators establish appropriate programs, facilities and services that promote, develop, and maintain a successful long-term relationship with both current and former students. This study proposes the use of a mediation model that links university entities and student loyalty via student satisfaction. A survey research design was used to collect data from 200 students of private universities in the Klang Valley, Malaysia. The data were then analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM). Upon analysis, it was found that student satisfaction was the major driver of student loyalty. The result also reveals that student satisfaction has fully mediated the relationship between academic facilities and student loyalty, whereas student satisfaction partially mediated the relationship between the support system and student loyalty. The study highlights the need for Higher Education Institutions (HEIs) to seriously acknowledge and focus in providing better university entities for students’ satisfaction as the satisfied students tend to be more loyal to make a comeback to the university.